PENGARUH NILAI INDIVIDU TERHADAP MINAT BERWIRAUSAHA MAHASISWA DI KOTA PALEMBANG - Maria Josephine Tyra; Andreas Sarjono (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2021)
Research entitled The Influence of Individual Values ​​on Student Entrepreneurial Interest in Palembang City to prove whether individual values ​​have an influence on students in Palembang for their interest in entrepreneurship. The data used are primary data. The data analysis technique used is quantitative including validity, reliability, descriptive analysis, classical assumption testing, and research hypothesis testing. The results of the study prove that the value of hedonism has a positive and significant effect on interest in entrepreneurship with a significance value of 0.009 < 0.05. This means that a hedonist has a great need to achieve personal success and pursue a pleasant life. Therefore, to motivate students in entrepreneurship requires a challenge in accordance with their expectations.